Learning from Los Curries: Photographing Tourists in Magaluf and Palma. Issue 1 (4th January 2019) - Stringer, Ben; McAllister, Jane
Photographic culture is a major part of the tourist experience, whether it is the drunken selfie posted in an online chatroom, or the carefully composed street scene published in an upmarket guidebook. The pictures shown here in this photographic study attempt to respond critically to the different dialectics of the camera, bodies, architecture, and light that prevail during the hours of night in Magaluf and Palma on the Spanish island of Mallorca. These images also aim to transgress the boundaries between the different visual cultures of these places because they seem to be outmoded in the way they socially categorise tourists, in what, on closer inspection, is evidently becoming part of a more 'liquid modernity' – to use Zygmunt Bauman's term – than the one that is still being portrayed. (Note: This paper expands upon themes raised in a short article previously published in 2015) [2 ].